Coupled experimental and computational investigation of omega phase evolution in a high misfit titanium-vanadium alloy. (15th May 2017) - Choudhuri, D.; Zheng, Y.; Alam, T.; Shi, R.; Hendrickson, M.; Banerjee, S.; Wang, Y.; Srinivasan, S.G.; Fraser, H.; Banerjee, R.
Abstract: Morphological and compositional evolution of omega (ω) precipitates in a model Titanium-20 wt%Vanadium (or 19 at.%V) alloy has been systematically investigated by coupling transmission electron microscopy and atom probe tomography with atomistic ab initio and continuum microelasticity computations. The initial water quenched microstructure comprised of a fine scale distribution of athermal ω precipitates, which form congruently from the β phase via a complete displacive collapse of 222β planes, that has been rationalized based on DFT computations. Subsequent annealing at 300 °C, over progressively increasing time periods, resulted in isothermal evolution of the ω precipitates, whose morphology changes from ellipsoidal to cuboidal, accompanied with V rejection. The highly V-enriched β matrix consisted of short VV bond lengths, further distorting the bcc lattice, and increasing the β/ω misfit. This facilitates the change in the morphology of omega precipitates from ellipsoidal to cuboidal resulting in a 001β habit plane for these precipitates. The coupled experimental and computational approach permits rationalizing the evolution of ω precipitate morphology and composition in such high β−ω misfit β-Ti alloys. Graphical abstract: Image